EFFECT OF TOOL WEAR ON MECHANICAL PROPERTIES OF FRICTION STIR WELDED AA2124/SiCp/25 COMPOSITE PLATES - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2011)
In this study, the presence of metals or compounds which might have been caused by the rotational tool wear tool manufactured from high speed steel in the stirring zone of FSWed similar AA2124/SiCp/25 composite joints has been investigated. The effects of low and high tool transverse speeds (40 and 100 mm min(-1)) on the tool wear were also evaluated. Microstructure investigations of the stirring zone by SEM, BEI and XRD were carried out. The experimental results show that the tool wear increased with increasing the tool transverse speed at the constant tool rotation speed. While the tool wear of the joints at 40 mm min(-1) was nearly unchangeable, the tool wear of the joints at 100 mm min(-1) clearly increased to 10% on the top and 5% on the root sections. In addition, XRD analysis shows that metallic particles broken down off from the stirring tool, SiO2 and Cu2FeAl7 intermetalic phases were detected in the stirring zone. It was concluded that the joining efficiency decreased to the rate of 42%.
Keywords: Friction stir welding (FSW); tool wear; AA2124/SiCp/25 composite; 6061+20-PERCENT AL2O3; MICROSTRUCTURES; OPTIMIZATION